Cerebral aneurysm occlusion at 12-month follow-up after flow-diverter treatment: statistical modeling for V&V with real-world data - Narata, Ana Paula (2021)
Background: Flow-Diverter (FD) porosity has been pointed as a critical factor in theocclusion of cerebral aneurysms after treatment.Objective: Verification and Validation of computational models in terms of predictivecapacity, relating FD porosity and occlusion after cerebral aneurysms treatment.Methods: Sixty-four aneurysms, with pre-treatment and follow-up images, wereconsidered. Patient demographics and aneurysm morphological information werecollected. The computational simulation provided by ANKYRAS provided FD porosity,expansion, and mesh angle. FD occlusion was assessed and recorded from follow-upimages. Multiple regression Logit and analysis of covariance (ANCOVA) models wereused to model the data with both categorical and continuous models.Results: Occlusion of the aneurysm after 12 months was affected by aneurysmmorphology but not by FD mesh morphology. A Time-To-Occlusion (TTO) of 6.92 monthson average was observed with an SE of 0.24 months in the aneurysm populationsurveyed. TTO was estimated with statistical significance from the resulting model forthe data examined and was capable of explaining 92% of the data variation.Conclusions: Porosity was found to have the most correction power when assessingTTO, proving its importance in the process of aneurysm occlusion. Still, further Verificationand Validation (V&V) of treatment simulation in more extensive, multi-center, andrandomized databases is required.